Pengaruh Model Pembelajaran Kooperatif Tipe Think Pair Share Berbantuan Media Flashcard terhadap Peningkatan Kemampuan Menulis Deskripsi Peserta Didik - Salma Zahida; Dini Riani; Arifin Ahmad (Mataram University, 2026)
The low descriptive writing skills of elementary school students remain a significant challenge, as classroom instruction is often teacher-centered and lacks learning models and media that effectively stimulate students' idea development. This study aimed to examine the effect of the Think Pair Share cooperative learning model assisted by Flashcard media on the descriptive writing skills of fourth-grade students at SDN Cijeruk 02. The study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of 56 fourth-grade students, divided into an experimental class and a control class, with 28 students in each group. Data were collected through tests, observations, and documentation, and analyzed using the Independent Sample t-test, N-Gain analysis, and effect size with IBM SPSS Statistics 29. The results revealed a significant effect of the Think Pair Share cooperative learning model assisted by Flashcard media on students' descriptive writing skills, indicated by a significance value of 0.001 (p < 0.05). The experimental group achieved an N-Gain score of 79.17%, categorized as effective, while the control group obtained an N-Gain score of 54%, categorized as less effective. Furthermore, the effect size was 0.9486, indicating a high level of practical effect. The novelty of this study lies in integrating the Think Pair Share cooperative learning model with Flashcard media to improve descriptive writing skills in elementary school students, providing a more effective instructional alternative than previous studies, which generally examined these two components separately. Therefore, the Think Pair Share cooperative learning model assisted by Flashcard media is proven to be effective in improving the descriptive writing skills of fourth-grade elementary school students.